2013
DOI: 10.1007/s10545-013-9610-6
|View full text |Cite
|
Sign up to set email alerts
|

Human and mouse neuroinflammation markers in Niemann‐Pick disease, type C1

Abstract: Niemann-Pick Disease, type C1 (NPC1) is an autosomal recessive lipid storage disorder in which a pathological cascade, including neuroinflammation occurs. While data demonstrating neuroinflammation is prevalent in mouse models, data from NPC1 patients is lacking. The current study focuses on identifying potential markers of neuroinflammation in NPC1 from both the Npc1 mouse model and NPC1 patients. We identified in the mouse model significant changes in expression of genes associated with inflammation and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 56 publications
11
67
0
Order By: Relevance
“…However, in contrast to decreased CSF holo-CP in AD, our analysis of the NP-C1 CSF revealed a modest but significant positive association between CSF total and holo-CP concentrations and disease severity (Figure 5A). CP is an acute phase marker and this association may reflect the increase in neuroinflammation in NP-C1 51 . Thus CSF CP may be a useful biomarker to monitor the disease progression and therapeutic response, in addition to the other CSF neuroinflammatory markers identified in the Cologna et al study 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to decreased CSF holo-CP in AD, our analysis of the NP-C1 CSF revealed a modest but significant positive association between CSF total and holo-CP concentrations and disease severity (Figure 5A). CP is an acute phase marker and this association may reflect the increase in neuroinflammation in NP-C1 51 . Thus CSF CP may be a useful biomarker to monitor the disease progression and therapeutic response, in addition to the other CSF neuroinflammatory markers identified in the Cologna et al study 51 .…”
Section: Discussionmentioning
confidence: 99%
“…CP is an acute phase marker and this association may reflect the increase in neuroinflammation in NP-C1 51 . Thus CSF CP may be a useful biomarker to monitor the disease progression and therapeutic response, in addition to the other CSF neuroinflammatory markers identified in the Cologna et al study 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory proteins corresponding to members of chemokines and cytokines family have been explored in cerebrospinal fluid of NPC patients; however, further investigation is required to establish their usefulness as biomarkers (54). Oxysterols largely reflect liver function, although 24(S)-HC has been proposed as a marker for neuronal disease in humans because it is produced in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…One further consideration is Niemann-Pick Disease Type C, which is a lysosomal storage disease leading to progressive organomegaly and neurologic dysfunction (3). Recent work has suggested that liver and neurologic dysfunction in Niemann-Pick is an inflammatory process, although signs of severe systemic inflammation as seen in this patient are uncommon (4). Additionally, liver biopsy did not show evidence for a storage disease.…”
Section: Case Presentationmentioning
confidence: 88%